Clinico-pathological changes associated with diaphragmatic hernia and foreign body syndrome in buffaloes - KAUR, TARJINDER; SINGH, BALWANT (The Indian Journal of Animal Sciences, 2013)
Clinico-pathological studies were undertaken on 16 cases of diaphragmatic hernia (DH) and 7 cases of foreign body syndrome (FRS). Haemoglobin concentration, TEc and pCv values were considerably less in 5 cases of DH and 4 cases of FBS. Anaemia in DH was macrocytic and normochromic. In FBS it was macrocytic and normochromic. Leucocytosis with reversal of neutrophil and lymphocyte ratio could be seen. Biochemical values revealed increase of SGOT, AIP and GGT in majority of cases under study. Protein level significantly decreased in almost all cases